The relevance of relevance: A review of Charles Forceville’s Visual and Multimodal Communication: Applying the Relevance Principle - Barratt, Daniel (Public Journal of Semiotics, 2025)
Relevance theory (RT), originally proposed by Sperber and Wilson (1986/1995), is a theory of human communication that is based on a general view of human cognition. In the classic version of RT, the paradigmatic example of human communication is a verbal exchange between a single speaker and a single hearer who are occupying the same space and time. In the book Visual and Multimodal Communication: Applying the Relevance Principle, Charles Forceville (2020) has two main goals: first, to make classic RT accessible to a wider (and non-expert) audience; and second, to adapt RT in order to account for other forms of communication beyond the purely verbal – namely, visual and multimodal communication. In the second half of the book, Forceville demonstrates how this adapted version of RT can be applied in a series of case studies on “static visuals”. In this extended review, I attempt to do justice to Forceville’s ambitious project and to outline the key concepts and terminology involved. In the discussion, I present some criticisms and questions, while offering some suggestions as to how adapted RT can be developed even further in order to account for moving images and film.